Screen video compression with a video card. Comparison of technologies - Druzhinin, D.V. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2008)
Two screen capture video compression algorithms, some operations of which are executed on GPU, are considered. A comparison of two technologies permitting to get access to the facilities of GPU (pixel shaders and NVidia CUDA) are discussed. Some results of testing the algorithms implemented on the basis of these technologies are given. The prospects for the further and wider usage of pixel shaders and NVidia CUDA in screen capture video compression are reviewed. Key words: video compression, pixel shaders, NVidia CUDA